중국인 유학생의 설명적 텍스트에 나타난 특징 분석 - 황선영 (언어와 문화, 2024)
This study aims to analyze textual features in compositions written by Chinese international students through the analysis of expository texts, exploring the influence of their native language on the writing. To achieve this, written compositions from 63 intermediate-level Chinese international university students were collected and analyzed using an inductive approach to categorize textual features by type. The research revealed that textual features in the writings of Chinese students could be broadly categorized into paragraph organization and conclusions. Within the domain of paragraph organization, issues were identified with sentence order and the insertion of unnecessary sentences. Furthermore, concluding sentences often exhibited characteristics such as personal content, new information, or functioning as central statements. Additionally, an analysis of Chinese elementary school textbooks was conducted to identify areas where learners' writing was influenced by their native language. Based on these findings, the study proposes educational recommendations for the content and methods of Korean writing courses designed for Chinese international university students. This research is significant in its analytical examination of authentic learner compositions to identify textual features, and its investigation of the impact of Chinese textbooks on the learners' writing. Furthermore, the study provides foundational material for the selection and instruction of educational content in academic-oriented writing courses for learners with a focus on language proficiency goals.
Keywords: 텍스트 특징; 텍스트성; 설명적 텍스트; 응집성; 중국인 유학생; 학문 목적 학습자; 텍스트 분석; Textual features(텍스트 특징); Textuality; Expository text; Coherence; Chinese international university Students; Academic purpose learners; Text analysis)